Enlightening progression of Paralympic Games : An overview study - Dutta, M. P.; Mahanta, S. D.; Das, D. M. (Indian Journal of YOGA Exercise & Sport Science and Physical Education, 2025)
A worldwide competition for people with various disabilities is the Paralympic Games. Ludwig Guttman organized this game in 1960 for veterans of World War II. Like an Olympic event, the game has greatly improved over time and is held every four years. The study aimed to demonstrate how the Paralympic Games have developed, resulting in a shift in perceptions of people with disabilities, improved accessibility and mobility and guaranteed equal chances for people with disabilities to participate in sports. Over time, there have been a lot more competitions, events, and participating countries. It now has a ton of brand-new games. There were 23, 8, and 400 participating nations, events, and athletes, respectively. However, as of right now, it is 162, 22, and 4333, respectively. The list of events has increased to twenty-two, including archery, athletics, Boccia, cycling (road & track), equestrian, football 5-a-side, football 7-a-side, goalball, judo, powerlifting, rowing, sailing, shooting, swimming, table tennis, sitting volleyball, wheelchair basketball, wheelchair tennis, wheelchair rugby, Paracanoe, badminton, and taekwondo. In 1960, the list of events required of athletes was just eight: archery, athletes, archery, snooker, swimming, wheelchair tennis, wheelchair basketball, and wheelchair fencing. The addition of these new games has inspired a lot of para-athletes. As a result, there have been more medal winners overall. There were 268 total medals won in 1960; by 2021, that number has increased to 1668.